Balancing Physical and Moral Development: A Study on the Core Values and Implementation Pathways of the Southwest Associated University Educators' Spirit in Cultivating Physical Education Teachers - Gu, Wei; Zhang, Jianyu; Li, Zhigang (International Journal of Social Sciences and Public Administration, 2025)
The spirit of educators at the Southwest Associated University represents a valuable legacy in China's educational history. Its core philosophy of “equal emphasis on physical fitness and moral character” holds significant implications for training physical education teachers in the new era. This paper addresses the demands placed on physical education teachers in the new era and the current dilemma of “prioritizing skills over spirit” in their training. Focusing on sports educators like John Mo from the Southwest Associated University, it delves into the institution's precious educational legacy of “equal emphasis on physical fitness and moral character.” The study demonstrates the core value of this spirit in cultivating physical education teacher candidates' professional ideals, educational capabilities, and sense of mission. Through historical research, theoretical analysis, and case studies, this paper delves into the essence and contemporary relevance of their educational spirit, explores effective pathways for integrating it into physical education teacher training, and provides theoretical references and practical guidance for building the physical education teacher workforce in the new era. The study distills three core values: historical reflection, theoretical guidance, and practical empowerment. Historical reflection emphasizes the inheritance of the “sports for national salvation” spirit; theoretical guidance highlights the contemporary relevance of John Mo's theory of transfer in physical education; and practical empowerment underscores the driving force of perseverance and resilience in educational practice. Simultaneously, the study analyzes current challenges in physical education teacher training, including utilitarian ideologies, fragmented resources, and monolithic methodologies. It constructs a three-stage progressive training system-cognitive construction, competency enhancement, and practical transformation-and establishes implementation pathways through technological empowerment, university-gymnasium collaboration, and cultural immersion. Findings indicate that the Southwest Associated University's educational spirit effectively enhances physical education teacher candidates' professional identity and comprehensive competencies, offering historical insights and practical paradigms for advancing high-quality physical education teacher training in the new era.